Laparoscopic Surgery in COVID-19 Era in a Tertiary Hospital in Nepal - Thapa, Ghanashyam; Nepal, Bikash (Nepalese Medical Journal, 2020)
Introduction: There is great concern and risk of transmission of COVID-19 infection from the aerosolized smoke during laparoscopic surgery although there is a lack of enough literature to prove this. To minimize these risks and get the benefi t of laparoscopic surgery, we used a low-cost fi ltration system connected to an underwater seal bag fi lled with a 5% sodium hypochlorite solution. Materials and Methods: This is a retrospective study of prospectively maintained data of cases of laparoscopic surgeries using a low-cost fi ltration device system connected with an underwater seal bag fi lled with 5% sodium hypochlorite solution. Use of personal protective equipment, minimal staff in operative theatre, preoperatively testing of patients before admission for surgery was done. During surgery, minimal use of electrocautery in low power setting maintaining low pneumoperitoneum and cautious desuffl ation of smoke during and end of the procedure from one of the trocars fi tted to heat and moisture exchanger Filter, connected through a tube to 5 % sodium hypochlorite solution in underwater seal bag was performed. Results: During the lockdown from May 2020 to October 2020, 41 elective laparoscopic surgeries were done. All patients were tested negative before the procedure. No staff in operation theatre developed symptoms of COVID-19 or tested positive for COVID-19 infection for up to 2 weeks period. Conclusions: In this Pandemic situation, we have to co-habit with this SARS-Cov-2 virus. Minimally invasive surgeries can be continued with safety measures with modifications like the use of low-cost filtration devices for smoke filtration and evacuation.